Experimental and theoretical approaches for thermomagnetic properties of CoFe-based flexible amorphous ribbons: shape anisotropy contribution - Casagrande-Denardin, J (ELSEVIER, 2026)
CoFe-based rapidly quenched amorphous ribbons are good model materials for studying the Anomalous Nernst Effect. They offer a promising platform to explore the efficiency of the converstion of thermal energy into electric energy, particularly compared to other sample geometries. However, the contribution of magnetic anisotropy to thermomagnetic properties plays a critical role in increasing the energy conversion efficiency for future technological applications. In this study, a flexible amorphous ribbon with the Co67Fe4Mo1.5Si16.5B11 composition, showing a strong in-plane shape magnetic anisotropy, was investigated through the Anomalous Nernst Effect (ANE) by varying both the intensity and angle of the external magnetic field, as well as the thermal gradient intensity. The microstructure and morphological features were analyzed, and the electrical properties were evaluated to elucidate their individual contributions to the thermomagnetic signal. A straightforward theoretical model was also proposed to predict magnetic and thermomagnetic responses in systems dominated by in-plane shape magnetic anisotropies. The CoFe-based amorphous ribbon experimentally reached an effective ANE coefficient (Seff) value of around 1.23 mu V/K. For the Anomalous Nerst coefficient (SANE), which considers the reduced temperature on the Co-base ribbon, the value is around 0.17 mu V/K. These results position Co67Fe4-Mo1.5Si16.5B11 amorphous ribbons as highly promising for thermal energy conversion and highly sensitive magnetic field detectors, among other applications.